2023
DOI: 10.1093/nar/gkad647
|View full text |Cite
|
Sign up to set email alerts
|

Single-worm long-read sequencing reveals genome diversity in free-living nematodes

Abstract: Obtaining sufficient genetic material from a limited biological source is currently the primary operational bottleneck in studies investigating biodiversity and genome evolution. In this study, we employed multiple displacement amplification (MDA) and Smartseq2 to amplify nanograms of genomic DNA and mRNA, respectively, from individual Caenorhabditis elegans. Although reduced genome coverage was observed in repetitive regions, we produced assemblies covering 98% of the reference genome using long-read sequence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 88 publications
1
9
0
Order By: Relevance
“…Considering that TEs represent 289 Mb of the 359-Mb genome, we can estimate that a large aspect of this genome was completely overlooked in the past. A recent study has shown that genome assemblies from basal nematodes contain more repeats (ranging from 23.4% up to 50.6% repeats) than nematodes belonging to other clades (ranging from 0.8 %p to 31%) [53]. The results here presented are consistent with the previousfindings as R. culicivorax , a basal nematode, showed a high repeat and TE content and the derived P. sp.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that TEs represent 289 Mb of the 359-Mb genome, we can estimate that a large aspect of this genome was completely overlooked in the past. A recent study has shown that genome assemblies from basal nematodes contain more repeats (ranging from 23.4% up to 50.6% repeats) than nematodes belonging to other clades (ranging from 0.8 %p to 31%) [53]. The results here presented are consistent with the previousfindings as R. culicivorax , a basal nematode, showed a high repeat and TE content and the derived P. sp.…”
Section: Discussionsupporting
confidence: 92%
“…This would result in fewer free 3’ ends of strands that could anneal to another strand and act as a primer to initiate chimera formation. As chimeric reads may be more problematic in data obtained from more fragmented template DNA, paired-end Illumina data generated from half of the specimen lysate before MDA could be used in future studies to aid in the detection of chimeras (see Lee et al 2023). Examining the mapping of paired-end short reads to post-amplification HiFi reads could be used to reveal chimeric reads as one of the reads in a pair would be expected to map on one side of the chimeric junction while its mate would be expected to map elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…MDA has been explored in the context of Oxford Nanopore (ONT) sequencing to produce relatively contiguous genomes from single nematodes (Lee et al 2023). For C. elegans , the authors generated an assembly consisting of 499 contigs with an N50 of 656.2 Kbp and a BUSCO completeness score of 97.6%, compared to 336 contigs with an N50 of 868.1 Kbp and a BUSCO score of 92.2% in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…several micrograms), typically thousands of times more than that which is contained within a single microscopic individual. Zhang et al (2019) proposed WGA in genome sequencing and phylogenomic of small animals, and two pioneering studies have used this method based on Illumina and PacBio platform to generate nematodes genomes (Lee et al, 2023;Doyle et al, 2019), although no study had yet evaluated its performance using microscopic species. In this study, we demonstrated that WGA generated smaller assembly and more fragmented contigs, probably due to the bias in the amplification process (Sabina et al, 2015).…”
Section: Whole Genome Amplification and Microscopic Eukaryotes Phylog...mentioning
confidence: 99%